Coverage enhancement and community empowerment via commercial availability of the long-lasting nets for malaria in India - Manju Rahi; Sundus Shafat Ahmad; Amit Sharma (Elsevier, 2021)
Achieving malaria elimination goal in India will require supplemental measures to plug in the gaps in implementation of malaria control programmes. Use of long-lasting insecticide nets is one of the two core interventions for vector control in malaria. The most common distribution channel is free delivery via national malaria control programme of various countries and in India, this is the only channel to provide nets to the masses. Understandably, there are gaps in the optimum coverage of at-risk population due to multiple reasons ranging from population growth to time lag in replacements, emergency conditions like floods and logistical impediments among others. At this juncture, it is crucial for India to explore complementary routes to expand access for nets by its people and one is making them available in private sector at an affordable price. The commercial availability of nets offers several advantages like filling in coverage gaps, overcoming additional requirements by families and financial resources being freed up for poor households. However, there are barriers to the successful operationalization of net commercialization like affordability issues, economic viability for manufacturers, regulatory issues etc. All the so-called barriers can be addressed in a concerted and pragmatic way to make access and availability of nets in private market a reality as that is a need of the hour, if India wants to achieve malaria elimination goal by 2030.